A Birth Cohort Study of Neurodevelopmental Outcomes from Birth to 2 Years of Age in Preterm Infants under 34 Weeks of Gestation. (13th April 2022) - Li, Hui-Li; Chen, Ling-Ling; Qian, Gang; Wang, Wei-Shi; Feng, Xiao-Na; Yu, Mei-Qiao; Ren, Lu-Zhong
Abstract : Background . The tissues and organs of premature infants are immature and easily damaged by external adverse factors, leading to functional development disorders and abnormalities. Besides, the incidence of premature babies in various countries has an increasing trend, with the incidence rate exceeding 10%. Objective . This study aims to investigate the neurodevelopment and the incidence of various developmental delays, cerebral palsy, autism spectrum disorder, and audio-visual impairment in premature infants under 34 weeks of gestation from birth to 2 years of age, so as to provide the basis for early intervention of premature infants in the clinic. Methods A cohort of premature infants was established using 263 premature infants with a gestational age of 28–33 + 6 weeks who were born alive from March 1, 2018, to February 28, 2019, in four tertiary hospitals in Shenzhen. In addition, 263 full-term infants of the same sex who were born in the same period in the four hospitals were randomly selected and paired in a ratio of 1 : 1 as the control group. The subjects were assessed for neurodevelopment using the Gesell test scale at 6, 12, 18, and 24 months after birth (premature infants were corrected for months). We calculated the neurodevelopmental indicators of children in each month of age and the incidence of various developmental delays, cerebral palsy, autism spectrum disorder, and audio-visual impairment in the two groups. Results The results of this study showed that the cohort of premature infants with birth gestational age less than 34 weeks had higher adaptive, fine motor, and personal-social energy domain development quotient (DQ) values from the corrected gestational age of 6 months to the corrected gestational age of 24 months after birth compared with the full-term cohort. And it also achieved catch-up growth in neurological development, but the detection rates of neurodevelopmental abnormalities at the corrected gestational age of 12 and 24 months were higher than those in the full-term cohort. Conclusion It is important to reduce the disability rate and degree of premature infants by strengthening the systematic management, early promotion and supervision, as well as early intervention for preterm infants with developmental abnormalities who were born at gestational age less than 34 weeks after birth.